White Jesus and Antisemitism: Toward an Antiracist and Decolonial Christology. - Hedges, Paul (Ecumenical Review, 2020)
This article argues that traditional Christology is intimately bound up with a triumphalist agenda that denies Jesus' Jewishness and is structurally antisemitic. Taking an antiracist stance, the article argues that systemic rethinking of Christianity's theological resources is needed, which must be anti‐antisemitic and antiracist. This involves reconfiguring how we take on board Jesus' Jewishness in a post‐Holocaust context and recognizing Jesus as a Jewish prophet. From this, it is tentatively suggested that rethinking the role of the Messiah involves understanding a Levinasian Messiah who does not come, but rather calls upon us to act in a Messianic role before the Other as an ethical imperative.